Factors Affecting Adoption of Organic Farming Technology in Arid Zone - Singh, Bhagwan; Sharma, A K (Annals of Arid Zone, 2020)
A study was conducted in arid region (Dantiwara village, Jodhpur district) of Rajasthan to identify major factors affecting the adoption of organic farming technology. A package of organic farming technologies was transferred to the farmers’ field through various extension methods viz., result demonstration, training, group discussion and distribution of literature. Eighty farmers were selected for the study from Dantiwara village of Jodhpur district. Study revealed that majority (55%) of the farmers belonged to medium adoption category followed by high (25%) and low adoption category (20%). Out of sixteen variables, ten variables i.e. education, caste, occupation, social participation, herd size, source of information, mass media exposure, knowledge, attitude and training received, were found to be positively and significantly correlated with the adoption of organic farming technology. Collectively the sixteen independent variables explained 59.8% of the variation in the adoption of organic farming technology. Key words: Organic farming technology, adoption, multiple regression analysis